2020
DOI: 10.1155/2020/6747498
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Effect of Nano-Hydroxyapatite in Demineralized Enamel before Orthodontic Bonding of Brackets and Attachments: Visual, Adhesion Strength, and Hardness in In Vitro Tests

Abstract: Dietary habits with high consumption of acidic food can induce in orthodontic patients an increased risk of demineralization lesions around orthodontic brackets and bands. The purpose of the present laboratory study is to assess the in vitro visual efficacy of a biomimetic nano-hydroxyapatite remineralizing solution in a hypomineralized enamel surface and its effect on adhesion of fixed orthodontic appliances and on enamel microhardness. Intact teeth were demineralized, and subsequently the areas of deminerali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 45 publications
1
80
0
1
Order By: Relevance
“…The Unit Internal Review Board approved this study. Forty freshly extracted bovine incisors were selected after meeting the inclusion criteria: integrity of the buccal surface, absence of enamel wear or caries, absence of anomalies of volume, shape and structure, and absence of traumatic lesions [24]. After being extracted, teeth were kept inside a solution of 0.1% (w/v) thymol free of alcohol, in complete darkness [25].…”
Section: Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Unit Internal Review Board approved this study. Forty freshly extracted bovine incisors were selected after meeting the inclusion criteria: integrity of the buccal surface, absence of enamel wear or caries, absence of anomalies of volume, shape and structure, and absence of traumatic lesions [24]. After being extracted, teeth were kept inside a solution of 0.1% (w/v) thymol free of alcohol, in complete darkness [25].…”
Section: Specimen Preparationmentioning
confidence: 99%
“…The preparation of the samples described above and the subsequent SBS test were performed according to previous studies [11,24]. Each sample was secured in the lower jaw of a universal testing machine (Model 3343, Instron, Canton, MA, USA) keeping the long axis of the splints parallel to the edge of the blade.…”
Section: Shear Bond Strength (Sbs) Testmentioning
confidence: 99%
“…Moreover, microcrystalline hydroxyapatite (HAP) particles were suggested as suitable candidates for the prevention of demineralisation and the stimulation of remineralisation process on www.nature.com/scientificreports/ tooth tissue 20,36 . It was reported that after nanohydroxyapathite treatment the enamel was more mineralised 37 and harder than demineralised enamel 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Biodentine is a bioactive dentine substitute material [ 2 ] that has been recommended for coronal, radicular restorations and in vital pulp therapy [ 8 ]. Biomimetic materials have been introduced in order to obtain a remineralizing effect on both dentine and enamel, showing promising results in terms of bond strength and tissue microhardness [ 21 ]. Strength of the bond between a final filling material and the underlined Biodentine is one of the most critical influences affecting the quality and success of the final restoration.…”
Section: Discussionmentioning
confidence: 99%